2017
DOI: 10.1093/ofid/ofw238
|View full text |Cite
|
Sign up to set email alerts
|

Serial Procalcitonin as a Predictor of Bacteremia and Need for Intensive Care Unit Care in Adults With Pneumonia, Including Those With Highest Severity: A Prospective Cohort Study

Abstract: Background.Procalcitonin (PCT) is a prohormone that rises in bacterial pneumonia and has promise in reducing antibiotic use. Despite these attributes, there are inconclusive data on its use for clinical prognostication. We hypothesize that serial PCT measurements can predict mortality, intensive care unit (ICU) admission, and bacteremia.Methods.A prospective cohort study of inpatients diagnosed with pneumonia was performed at a large tertiary care center in Boston, Massachusetts. Procalcitonin was measured on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
0
8
1
Order By: Relevance
“…Though many investigators have studied the utility of PCT in predicting mortality in various types of pneumonia including CAP [57, 1726], HCAP [37, 38], VAP [3943] and HAP [44], their results were not consistent While some reported PCT to be a reliable predictor for mortality [1726], others showed that PCT was inferior to other markers such as PSI, CURB-65 [52], CRP, IL-6 [53], or BUN/albumin ratio [54] for predicting mortality. Several investigators reported that serial measurements of PCT were useful for predicting mortality [21, 50, 55]. In the present study, PCT did not remain an independent prognostic factor in the younger and elderly patients in our multivariate analysis.…”
Section: Discussioncontrasting
confidence: 59%
“…Though many investigators have studied the utility of PCT in predicting mortality in various types of pneumonia including CAP [57, 1726], HCAP [37, 38], VAP [3943] and HAP [44], their results were not consistent While some reported PCT to be a reliable predictor for mortality [1726], others showed that PCT was inferior to other markers such as PSI, CURB-65 [52], CRP, IL-6 [53], or BUN/albumin ratio [54] for predicting mortality. Several investigators reported that serial measurements of PCT were useful for predicting mortality [21, 50, 55]. In the present study, PCT did not remain an independent prognostic factor in the younger and elderly patients in our multivariate analysis.…”
Section: Discussioncontrasting
confidence: 59%
“…The study found that for the total population at PCT values of 0.1, 0.25, and 0.5 ng/mL, sensitivity was 63%, 54%, and 46%, respectively, for the composite endpoint, all with negative predictive value >80%. The specificity of PCTbased prognosis using these cut-offs was highest when evaluating the HCAP subpopulation, whereas sensitivity was highest in the CAP group [48].…”
Section: Procalcitonin As a Prognostic Indicator In Hapmentioning
confidence: 96%
“…Several studies have shown PCT to be useful as a prognostic indicator in patients with pneumonia. The studies were predominantly conducted among patients with community-acquired pneumonia (CAP) [19,[36][37][38][39][40][41][42][43][44][45][46][47][48], healthcare-associated pneumonia (HCAP) [20,48,49] and HAP/VAP [31,32,[50][51][52][53][54][55][56]. In the most recently published study, Hong DY et al, [20] used PCT in HCAP patients to determine its efficacy as an indicator for predicting mortality.…”
Section: Procalcitonin As a Prognostic Indicator In Hapmentioning
confidence: 99%
“…8 In a 2017 study of 317 adults hospitalized with pneumonia, the PCT level was significantly higher in those with bacteremia and in those admitted to intensive care. 9 When used in combination with the pneumonia severity index (PSI), the ad-dition of PCT resulted in improved prognostic performance compared with the PSI alone for both outcomes, increasing the area under the receiver operating characteristic curve from 0.67 to 0.85 for bacteremia and from 0.58 to 0.64 for intensive care. Similarly, in the adult EPIC cohort, the addition of PCT contributed significant prognostic information beyond existing severity scores for predicting the need for invasive respiratory or vasopressor support; each 1 µg/L increase in PCT was associated with a 1% to 2% absolute increase in the need for this outcome.…”
Section: Procalcitonin For Severity Prediction In Lrtimentioning
confidence: 99%